Pengaruh Penerapan Service Quality terhadap Kepuasan melalui Kepercayaan Nasabah BSI Mobile (Studi Kasus: UIN Sunan Kudus) - Dea Aprilia; Kharis Fadlullah Hana (At-Taradhi Jurnal Studi Ekonomi, 2026)
This study examines the effect of service quality on customer trust, with customer satisfaction acting as a mediating variable, among BSI Mobile users at UIN Sunan Kudus. Prior studies in this field have consistently treated satisfaction as an outcome of service quality and trust as an antecedent of satisfaction, but rarely tested — and sometimes mislabeled — the specific mediating role that satisfaction plays in translating service quality into trust for a young, digitally native customer segment. This gap motivated the present study. A quantitative associative approach was employed using Partial Least Squares Structural Equation Modelling (PLS-SEM), with data collected from 100 respondents selected through purposive sampling. The results indicate that service quality has a positive and significant effect on customer satisfaction, and that customer satisfaction, in turn, has a positive and significant effect on customer trust. Furthermore, service quality exerts a significant indirect effect on customer trust through customer satisfaction as a mediating variable. These findings confirm that customer satisfaction functions as a critical link between service quality and trust formation in a digital banking context, offering theoretical refinement of the service-quality-satisfaction-trust chain and practical direction for Islamic digital banking providers.